2008
DOI: 10.1016/j.neuron.2008.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Matching Categorical Object Representations in Inferior Temporal Cortex of Man and Monkey

Abstract: SUMMARY Inferior temporal (IT) object representations have been intensively studied in monkeys and humans, but representations of the same particular objects have never been compared between the species. Moreover, IT’s role in categorization is not well understood. Here, we presented monkeys and humans with the same images of real-world objects and measured the IT response pattern elicited by each image. In order to relate the representations between the species and to computational models, we compare response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

95
1,457
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,267 publications
(1,605 citation statements)
references
References 72 publications
95
1,457
12
1
Order By: Relevance
“…While the visual cortex of BNNs may use quite different learning algorithms, its objective function to be minimised may be quite similar to the one of visual ANNs. In fact, results obtained with relatively deep artificial DBNs (Lee et al, 2007b) and CNNs (Yamins et al, 2013) seem compatible with insights about the visual pathway in the primate cerebral cortex, which has been studied for many decades (e.g., Hubel and Wiesel, 1968;Perrett et al, 1982;Desimone et al, 1984;Felleman and Van Essen, 1991;Perrett et al, 1992;Kobatake and Tanaka, 1994;Logothetis et al, 1995;Bichot et al, 2005;Hung et al, 2005;Lennie and Movshon, 2005;Connor et al, 2007;Kriegeskorte et al, 2008;DiCarlo et al, 2012); compare a computer vision-oriented survey (Kruger et al, 2013).…”
Section: Consequences For Neurosciencementioning
confidence: 81%
“…While the visual cortex of BNNs may use quite different learning algorithms, its objective function to be minimised may be quite similar to the one of visual ANNs. In fact, results obtained with relatively deep artificial DBNs (Lee et al, 2007b) and CNNs (Yamins et al, 2013) seem compatible with insights about the visual pathway in the primate cerebral cortex, which has been studied for many decades (e.g., Hubel and Wiesel, 1968;Perrett et al, 1982;Desimone et al, 1984;Felleman and Van Essen, 1991;Perrett et al, 1992;Kobatake and Tanaka, 1994;Logothetis et al, 1995;Bichot et al, 2005;Hung et al, 2005;Lennie and Movshon, 2005;Connor et al, 2007;Kriegeskorte et al, 2008;DiCarlo et al, 2012); compare a computer vision-oriented survey (Kruger et al, 2013).…”
Section: Consequences For Neurosciencementioning
confidence: 81%
“…conceptual vs perceptual) drove the observed discriminations (Simanova et al, 2014). A second approach, representational similarity analysis (RSA) (Kriegeskorte et al, 2008), compares the similarity between different stimuli and the one observed between the multivoxel activations patterns elicited by them (i.e. neural similarity).…”
Section: Multivariate Pattern Analysesmentioning
confidence: 99%
“…Direct visual inspection of RDMs may yield clustered structures in neural response patterns [22,23]. Nevertheless, the dissimilarity structures can be measured and analyzed by automated algorithms of multi-dimensional scaling (MDS) [24] and hierarchical clustering analysis [25].…”
Section: Representing Dissimilarity Structure Of Response Patterns Tomentioning
confidence: 99%
“…The authors found, contrary to previous studies [29,30], that representations in the ventral temporal parahippocampal place area (PPA) were characterized primarily by the spatial factor of expanse (open, closed) and in early visual cortex (EVC) primarily by distance (near, far), not by category or context. Kriegeskorte et al [22] applied hierarchical clustering analysis of response patterns in human brain evoked by 92 ungrouped-object stimuli photos, and found that object representation was inherently categorical in inferotemporal cortex (IT): animate and inanimate objects form the two major clusters; faces and bodies form subclusters within the animate cluster.…”
Section: Representing Dissimilarity Structure Of Response Patterns Tomentioning
confidence: 99%
See 1 more Smart Citation